Design of an Arduino-Based Smart Home Security System Using PIR Sensors and Mobile Notifications - Muhammad Wahyu; M.Ilham Ramadhan; Puspita Sari Br Ginting; Adinda Zona Patrisia; Asprina Br. Surbakti; Siti Jamilah Br Tarigan (JCEIT: Journal of Computer Engineering and Information Technology, 2025)
This research aims to develop a home access security system with a combination of Arduino-based sensors and buzzer methods and to address the problem of home downtime. This research has 3 methods, namely observation, laboratory research, and library study. This study was created to develop a tool for detecting a car using a PIR sensor that can be controlled using a smartphone and notifications directly go to the Telegram application that can be monitored anywhere and anytime, so that when homeowners live for a long period of time they are not too worried while the tool we created uses sensors located on 4 sides of the house. In the design of this tool, the author hopes that it can be developed to be more sophisticated and have even more useful benefits. REFERENCES Annisa, D., Jannah, R., Pebriana, R., Wulandari, S., Ihsan, M. Z., & Anisa, N. (2024). RANCARAN PENERAPAN IOT UNTUK SISTEM ALARM ANTI MALING MENGGUNAKAN SENSOR PIRArifin, J., Frenando, J., & Herryawan, H. (2022). Sistem Keamanan Pintu Rumah Berbasis Internet of Things via Pesan Telegram. TELKA - Telekomunikasi Elektronika Komputasi Dan Kontrol, 8(1), 49–59. https://doi.org/10.15575/telka.v8n1.49-59Desvira Annisa, Raudhatul Jannah, Risky Pebriana, Sefti Wulandari, M. Zufannor Ihsan, & Nor Anisa. (2025). RANCARAN PENERAPAN IOT UNTUK SISTEM ALARM ANTI MALING MENGGUNAKAN SENSOR PIR. KOMNET : Jurnal Komputer, Jaringan Dan Internet. https://doi.org/10.34128/5wv4aw69Haidar, A., Elisma, E., Yamin, M., & Pertiwi, W. P. (2024). Sistem keamanan pintu rumah berbasis aplikasi Telegram dan Internet of Things (IoT). JITEL (Jurnal Ilmiah Telekomunikasi, Elektronika, Dan Listrik Tenaga), 4(2), 137– 144. https://doi.org/10.35313/jitel.v4.i2.2024.137-144Kango, R., Abas, M. I., & Finanto, H. (2022). Rancang Bangun Sistem Keamanan Rumah Berbasis Internet of Things. JTT (Jurnal Teknologi Terpadu), 10(2), 136–141. https://doi.org/10.32487/jtt.v10i2.1565Majumder, A. J., & Izaguirre, J. A. (2020). A Smart IoT Security System for Smart-Home Using Motion Detection and Facial Recognition. 2020 IEEE 44th Annual Computers, Software, and Applications Conference (COMPSAC), 1065–1071. https://doi.org/10.1109/COMPSAC48688.2020.0-132Mujitomo, M. T. A., Santoso, H., Widyawati, L., & Priyanto, D. (2022). Home Security Voice Notification System With Arduino Sensor, PIR based SMS Gateway. International Journal of Engineering and Computer Science Applications (IJECSA), 1(1), 1–8. https://doi.org/10.30812/ijecsa.v1i1.1793Muttaqin, I. R., & Santoso, D. B. (2021). Prototype Pagar Otomatis Berbasis Arduino Uno Dengan Sensor Ultrasonic Hc-SR04. JE-Unisla, 6(2), 41. https://doi.org/10.30736/je-unisla.v6i2.695Putra Pratama, M. P., & Martias, M. (2023). Alat Keamanan Menggunakan Sensor Gerak Dengan ESP32 Cam Berbasis Iot. INSANtek, 4(2), 69–76. https://doi.org/10.31294/insantek.v4i2.2117Rahmat, S., & Yanti, F. (2022). Alat Pendeteksi Keberdaan Manusia Otomatis Berbasis Mikrokontroler Arduino Uno Dengan Menggunakan Sensor PIR (Passive Infrared). 2(3).Samuel Hasudungan Nababan. (2024). Sistem Keamanan Ruangan Menggunakan Sensor PIR dan Modul GSM SIM Berbasis Arduino Uno. Vol. 6 No. 1 Thn 2024 Hal 70-79.Shokrollahi, A., Persson, J., Malekian, R., Sarkheyli-haegele, A., & Karlsson, F. (2024). PIR Sensor-Based Occupancy Monitoring in Smart Buildings: A Review of Methodologies and Machine Learning Approaches. https://doi.org/10.20944/preprints202401.1924.v1Susanto, R., Husen, M. N., & Lajis, A. (2022). The Product Development of Portable Laboratory Integrated with Local Wisdom (PL-ILW) by Undergraduate Student. 2022 16th International Conference on Ubiquitous Information Management and Communication (IMCOM), 1–5. https://doi.org/10.1109/IMCOM53663.2022.9721731Wisnu Wiraditama, Dedi Candra, Ami Prasena Nugraha, & Sulartopo Sulartopo. (2023). Sistem Keamanan Rumah Menggunakan Sensor Passive Infrared. Seminar Nasional Teknologi Dan Multidisiplin Ilmu (SEMNASTEKMU), 3(1), 200–210. https://doi.org/10.51903/semnastekmu.v3i1.215